Efektifitas Buah Pepaya (Carica Papaya L) Terhadap Peningkatan Produksi ASI Pada Ibu Menyusui - Purwandari, Atik; Tombokan, Sandra Grace Jelly; Nangkoda, Natalia; Wahyuni, Wahyuni; Lontaan, Anita; Pesak, Ellen; Tuju, Sjenny Olga (JIDAN Jurnal Ilmiah Bidan, 2025)
Background: Breast milk (ASI) production is a common factor and a key determinant in the success of breastfeeding. Many mothers often complain that their breast milk either does not come out or is produced in small quantities. Although breast milk has tremendous benefits, not many mothers are willing or able to provide exclusive breastfeeding for six months. The failure to provide exclusive breastfeeding can be influenced by the lack of nutritional support. Several studies have indicated that papaya (Carica papaya) has the potential as a natural galactagogue that can stimulate breast milk production. The bioactive compounds in papaya, such as the enzyme papain, vitamin A, vitamin C, flavonoids, and other phytochemicals, are known to support metabolism and tissue health, including the mammary glands. Objective: To analyze the effectiveness of papaya (Carica papaya L) in increasing breast milk production among breastfeeding mothers at Kauditan Public Health Center, North Minahasa Regency. Method: This study used a quasi-experimental design with a non-randomized pre-test and post-test approach. A total of 35 respondents were selected using purposive sampling. Normality was tested using the Shapiro-Wilk test, which showed that the data were not normally distributed (p < 0.05), so the Wilcoxon test was used. Results: The Wilcoxon test showed a significant difference in breast milk production before and after papaya consumption (p = 0.000 < 0.05). Most mothers produced less than 80 ml of breast milk before the intervention, increasing to 80–150 ml afterward. Variations in milk production were influenced by individual nutritional status; thus, support from husbands and families is essential to meet the nutritional needs of breastfeeding mothers. Conclusion: Papaya is effective in increasing breast milk production in breastfeeding mothers. It is recommended that mothers consume papaya regularly during breastfeeding to help enhance milk production.